DEEP Study: Indirect and Out-of-pocket Costs of Persistent Orofacial Pain. (October 2018) - Breckons, M.; Shen, J.; Bunga, J.; Vale, L.; Durham, J.
Persistent orofacial pain (POFP) is common and caused by a group of conditions affecting the face, head, or mouth. Recent research highlighted a problematic care pathway with high costs to the health care provider, but the financial impact on patients and employers is not understood. This study aimed to describe patient (out-of-pocket) and employer (indirect) costs of POFP and to identify whether the dichotomized Graded Chronic Pain Scale (GCPS) was predictive of costs. A cohort of 198 patients was recruited from primary and secondary care settings in North East England and followed over a 24-mo period. Patients completed the GCPS and Use of Services and Productivity Questionnaire every 6 mo and a Time and Travel Questionnaire at 14 mo. Questionnaires examined the implications of health care utilization on patients' everyday lives and personal finances. Time and travel costs were calculated and applied to use-of-services data to estimate out-of-pocket costs, while the human capital method and QQ method (quantity and quality of work completed) were used to estimate absenteeism and presenteeism costs, respectively. Per person per 6-mo period (in 2017 pounds sterling), mean out-of-pocket costs were £333 (95% CI, £289 to £377), and indirect costs were £1, 242 (95% CI, £1, 014 to £1, 470). Regression analyses indicated that over 6 mo, the GCPS was predictive of the following: out-of-pocket costs—a difference of £311 between low and high GCPS per person per 6-mo period (95% CI, £280 to £342; P < 0.01, n = 705 observations over 24 mo); indirect costs—a difference of £2, 312 between low and high GCPS per person per 6-mo period (95% CI, £1, 886 to £2, 737; P < 0.01; n = 352 observations over 24 mo). This analysis highlights "hidden" costs of POFP and supports the use of the dichotomized GCPS to identify patients at risk of higher impact and associated costs and thereby stratify care pathways and occupational health support appropriately.